Redescription of Porcellio brevicaudatus Brandt, 1833 (Isopoda: Oniscidea); with some notes on other synonyms of Hemilepistus reaumurii (Milne-Edwards, 1840) - Kashani, Ghasem M.; Wägele, Johann-Wolfgang; Schmalfuss, Helmut (Zootaxa, 2011)
In the present study, Porcellio brevicaudatus Brandt, 1833 is resurrected and redescribed. It is shown that Hemilepistus sottii Arcangeli, 1932, H. rostratus Arcangeli, 1932 and H. patrizii Brian, 1932, currently synonyms of H. reaumurii (Milne-Edwards, 1840), are conspecific with P. brevicaudatus. The other synonyms of H. reaumurii are reinvestigated based on type material or comparison with descriptions. Porcellio syriacus Koch, 1847, Hemilepistus bodenheimeri Verhoeff, 1931, H. palaestinus Verhoeff, 1931 and Paraniambia tuberculata Collinge, 1914 are confirmed as synonymies.